An Eulogy to Father Alexei Mateevich (Confluenţe Bibliologice, 2017)
The author reports about the activities carried out during the festival dedicated to Alexei Mateevici, the father of Romanian language. 129 years have passed since the poet's birthon March 27, 2017. On this occasion at the school in Donduşeni that bears his name occurred the seminar ofteachers of Romanian and literature languagefrom district. A recital of poems from the poet's work attended by the V-VIII grade students was organized on March 28th.
Keywords: Alexei Mateevici (1888 – 1917); school library